Crystal Structure Induced Ultralow Lattice Thermal Conductivity in Thermoelectric Ag9AlSe6. Issue 18 (25th March 2018) - Li, Wen; Lin, Siqi; Weiss, Manuel; Chen, Zhiwei; Li, Juan; Xu, Yidong; Zeier, Wolfgang G.; Pei, Yanzhong
Abstract: Recent discoveries of novel thermoelectric materials largely rely on an intrinsic low lattice thermal conductivity. This results from various mechanisms including low sound velocity, complex crystal structure, liquid‐like ions, and lattice anharmonicity. Here semiconducting Ag9 AlSe6 with many weakly bonded and highly disordered cations is shown to be a promising novel thermoelectric material, due to its ultralow lattice thermal conductivity (κL ) of ≈0.3 W m −1  K −1 in the entire temperature range. Such a low κL is believed to be a result of its (1) complex crystal structure for a small population of acoustic phonons, (2) soft bonding for an overall low sound velocity (1300 m s −1 ), and (3) massive disordering of Ag ions. Its electronic transport properties can be well understood by a single parabolic band model with acoustic scattering. The achieved thermoelectric figure of merit ( zT ) can be as high as unity, which is unlike conventional thermoelectric materials, which rely heavily on a high power factor. This work not only demonstrates Ag9 AlSe6 as a promising thermoelectric material, but also paves the way for the exploration of novel thermoelectrics with a complex crystal structure with weakly bonded and highly disordered constituent elements in the structure. Abstract : A complex crystal structure, soft bonding, and disordering lead to an ultralow lattice thermal conductivity in a novel thermoelectric material Ag9 AlSe6 showing a peak zT of unity. This paves the way for the exploration of novel thermoelectrics via a crystal structure design.